2021
DOI: 10.1136/archdischild-2020-320966
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of neonatal hypoxic-ischaemic encephalopathy in centres with and without active therapeutic hypothermia: a nationwide propensity score-matched analysis

Abstract: ObjectiveTherapeutic hypothermia (TH) for neonatal hypoxic-ischaemic encephalopathy (HIE), delivered mainly in tertiary cooling centres (CCs), reduces mortality and neurodisability. It is unknown if birth in a non-cooling centre (non-CC), without active TH, impacts short-term outcomes.DesignRetrospective cohort study using National Neonatal Research Database and propensity score-matching.SettingUK neonatal units.PatientsInfants ≥36 weeks gestational age with moderate or severe HIE admitted 2011–2016.Interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
(18 reference statements)
1
10
0
Order By: Relevance
“…Despite various criteria de ning optimal TH in the literature [16] (time to reach an optimal therapeutic temperature [12], or temperature at admission in therapeutic range [17]), and the extension of TH to less severe NE [18], our results of 70.2% of neonates reaching a rectal temperature within optimal range before 6 hr, is in line with data in the literature. In an early study from The Netherlands and Flanders, TH, indicated with "clear presence of perinatal asphyxia followed by neonatal encephalopathy", was started later than 6 hr after birth in 4.8% of infants [16].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Despite various criteria de ning optimal TH in the literature [16] (time to reach an optimal therapeutic temperature [12], or temperature at admission in therapeutic range [17]), and the extension of TH to less severe NE [18], our results of 70.2% of neonates reaching a rectal temperature within optimal range before 6 hr, is in line with data in the literature. In an early study from The Netherlands and Flanders, TH, indicated with "clear presence of perinatal asphyxia followed by neonatal encephalopathy", was started later than 6 hr after birth in 4.8% of infants [16].…”
Section: Discussionsupporting
confidence: 89%
“…In the United Kingdom, proportions of infants achieving optimal therapeutic temperatures at admission in a CC increased from 60.8% in 2011 to 76.0% in 2016 [12]. During the same period, 67.1% of UK neonates born in a non-CC arrived with a temperature between 33 and 34°C [17]. Data using the UK national neonatal research database have allowed to describe more precisely factors associated with delayed timing [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal studies support early TH (<3 hours of age) with less neuronal loss and better neuroprotection compared with late (3–6 hours) or delayed (>6 hours) treatment 17 18 20 40. This is supported by observational human data showing better motor development19 and less occurrence of seizures 41 42. Seizures associated with HIE can increase the long-term risk of a poor neurodevelopmental outcome 43–45.…”
Section: Discussionmentioning
confidence: 85%
“…Although there has never been a controlled clinical trial of the timing of initiation of therapeutic hypothermia, in a cohort of 76 infants recruited using the CoolCap/TOBY protocols, treatment before 3 hours of age was associated with improved psychomotor developmental index scores (Bayley Scales of Infant Development II) at 18 months compared with cooling from 3 to 6 hours 17. Moreover, there is evidence that infants with HIE born in a centre that offers therapeutic hypothermia onsite have improved seizure-free survival, presumptively due to earlier initiation of treatment 18. Hypothermia was initiated in HELIX at a median of 4.30 hours after birth (IQR 1.09–6.00), similar to previous trials.…”
mentioning
confidence: 98%